Innovation or Consumption: A Critical Approach and A Qualitative Analysis to Innovative Consumption - Özdemir, Özge Gökbulut; Özer, Deniz (Beta Basım Yayım Dağıtım A.Ş. [EN], 2014)
In 19th century, many developments in many areas, such as technological, scientific, economic, social, cultural and political, has occured. These developments blow away the history of humanity to a process indexing everything to innovation. Phenomena such as industrial revolution, rising of capitalism, series production and urbanization has accelarated the production and consumption relations. The dominant previous consuption approach in the focus of vital needs has given its place to an approach focusing on beyond the neccesity consumption. Whilst the expansion of ‘needs’ concept, new consumption presented in the name of “innovation” and the individuals has been codded as ‘consumer’ and encouraged through the possitive images imputed to ‘innovation’. So that, while innovation labels the production side of 21th century, ‘consumer society’ providing the sustainablity of the innovation keeps to build the social profile of the 21th century dramaticaly. Whilst not denying the role of innovation in the economic development, the paradox between consumption and innovation is discussed basing on ‘culture industry’ and an emprical research is presented. In the research, the perception and opinion about “Consumer Society” and “Innovative Consumption” is investigated in terms of the perception of post-graduate students in the field of “Entrepreneurship and Innovation Management”. 56 of 63 students has reached and the data obtained from interviews and content analysis method is evaluated. Results demonstrate that the participants distinguished the term ‘consumer society’ from ‘innovative consumer’. They critisize the ‘consumer society’ while emphasis the benefits of innovation.

19. yüzyılda teknolojik, bilimsel, ekonomik, sosyal, kültürel ve siyasal alanda birçok gelişme yaşanmış; bu gelişmeler insanlık tarihini her şeyin hıza ve yeniye endekslendiği bir sürece sürüklemiştir. Sanayi devrimi, yükselen kapitalizm, seri üretim, kentlileşme gibi olgular üretim ve tüketim ilişkilerine ivme kazandırmış; geçmişte hâkim olan ihtiyaç doğrultusunda üretme ve tüketme anlayışı yerini ‘zorunlu ihtiyaç’ ötesi tüketim anlayışına bırakmıştır. ‘İhtiyaç’ kavramının sınırları genişlerken, tüketici için ihtiyaç olanın ötesi ‘yenilik’ adı altında sunularak; ‘tüketici’ olarak kodlanan bireyler yeniliğe atfedilen olumlu imajlar aracılığıyla yeni olana ve ‘yenilik’ e özendirilmektedir. Öyle ki ‘yenilik’ üretim cephesinde 21. Yüzyıla damgasını vururken, yeniliğin sürdürülebilirliğini sağlayan ‘tüketim toplumu’ da dramatik bir hızla 21. Yüzyılın sosyal profilini oluşturmaya devam etmektedir.Çalışma ‘yeniliğin ekonomik gelişmedeki rolünü yadsımazken, tüketim ve yenilik konusundaki paradoksları ‘kültür endüstrisi’ bağlamında kavramsal olarak tartışmanın yanı sıra nitel bir araştırma da sunmaktadır. “Tüketim Toplumu” ve “Yenilikçi Tüketim” ile ilgi algı ve düşünce “Girişimcilik ve Yenilik Yönetimi” alanında lisansüstü eğitim alan yetişkinler özelinde araştırılmıştır. 63 kayıtlı öğrencinin 56’ sına ulaşılmış; bireylere ‘tüketim toplumu’ ve ‘yenilikçi tüketim’ konusuyla ilgili görüşleri sorulmuştur. Görüşmelerden elde edilen veriler kategoriler oluşturularak; içerik analizi yöntemiyle değerlendirilmiştir. Araştırma sonunda, katılımcıların ‘tüketim toplumu’ kavramını ‘yenilikçi tüketim’ kavramından farklı algılayarak eleştirirken; yeniliğin insanlara fayda sağladığı konusuna vurgu yaptıkları görülmektedir
Yenilikçilik mi? Tüketim mi?: Yenilikçi Tüketime Eleştirel Bir Yaklaşım ve Nitel Bir Analiz